COVID-19 pandemic afflicts lifestyle and dietary habits of female university students - Khattab, Rabie; Al-Alwy, Shimaa; Al-Ateeq, Taef; Al-Hwiesh, Reema; Al-Saeed, Batool; Al-Tuwairish, Mezoun; Al-Rubaian, Sadeem; Goja, Arafat; Al-Otaishan, Sara; Purayidathil, Tunny; Abuzaid, Omar (International Journal Of Community Medicine And Public Health, 2022)
Background: Coronavirus (COVID-19) pandemic has triggered a profound effect on all aspects of society, including mental and physical health in Saudi Arabia and over the globe. The pandemic has put a spotlight on the important role of nutrition in supporting the immune system relative to viral infections. The application of physical separation was the main scale used worldwide to fight COVID-19. Unavoidable nationwide cultural intercessions, such as lockdown, curfew and quarantine, imposed by the governments, resulted in unexpected outcomes such as financial difficulties, economic burden, changes in lifestyle and dietary habits, and the breakdown of psychosocial and metabolic well-being. Methods: This cross-sectional study was conducted to evaluate the impact of COVID-19 pandemic on lifestyle and dietary habits among female university students in Saudi Arabia. Three hundred (300) participants aged 18-25 years were randomly recruited using convenient sampling. A structured self-administrated online questionnaire was used to collect the information on lifestyle, physical activity, health history and dietary habits. We hypothesized that the pandemic and its consequent restriction measures would adversely impact the lifestyle and dietary habits of students. Results: There was a significant association between lockdown and weight gain (p<0.001) with 65% of participants reporting 5-11 kg weight gain during the pandemic. Lifestyle change, availability of food at home and stress/anxiety due to COVID-19 were the most common factors reported for weight gain (47%, 29% and 19%, respectively). A significant association (p<0.001) was found between screen time and COVID-19 lockdown with more than 10 hours spent in front of screens. Similarly, a significant change (p<0.001) was reported in food consumption and dietary behaviour during COVID-19. Most participants consumed home-made food (94%) while only 4% consumed foods from outside and 2% consumed fast food from restaurants. Conclusions: COVID-19 had a negative impact on lifestyle changes, dietary habits and physical activity, which was associated with significant weight gain among Saudi university students. This effect is attributed to the restriction measures that decreased the physical activity, and the psychological aspects that affected the quality and quantity of food consumed. Increasing awareness, healthy dietary plans and physical activity are highly recommended during the pandemic.